Pengetahuan Lokal Sub-Etnis Batak Toba dalam Memanfaatkan Tumbuhan Obat (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2023)
Knowledge of the utility of medicinal plants in sub-ethnicity of Batak Toba has not been widely disclosed. This knowledge has been passed down from generation to generation orally and has very limited documentation so it has the potential to be lost. The result of this study are intended to reveal the local's knowledge of the utilization of medicinal plants by Batak Toba sub-etnicity in Desa Sipagabu. The methods of collecting the data were done by conducting semi-structured interviews and participatory observation with the informant. Descriptive statistics have been used to analyze the collected data. In this study, the informant consisted of 51 natives Batak Toba sub-ethnicity with previous knowledge of the utilization of medicinal plants. Medicinal plants that were used are 115 species which belong to 100 genus and 49 families. The main families of medicinal plants utilized by local comunities are Asteraceae, followed by Fabaceae and Zingiberaceae, and Poaceae.  Medicinal plants were used to cure disease are grouped into natural diseases, supranatural disease, uncommon disease, and certain diseases that are cure using traditional concotion.